The Effect of Cost Determination in the Provision of Halal Certificates on Traded Products in Makassar City - Azzah Azimah Assagaf; Juajir Sumardi; Winner Sitorus (Khazanah Hukum, 2022)
In terms of food or goods and their use, Islam commands its followers to eat and use good, holy, and clean ingredients. Allah Subhanahu Wa Ta'ala says which means: "O mankind, eat what is lawful and good from what is on earth, and do not follow the steps of the devil, because indeed the devil is a real enemy for you." (Q.S. Al-Baqarah, 2:168). In other words, the concept of perfect and recommended food is â€œhalal and good food.â€ Since the Covid-19 pandemic has spread throughout Indonesia, many have turned into traders to provide for themselves and their families due to mass layoffs. However, if you want to sell, you need to pay attention to the composition that will be used, because in Article 4 of Law Number 33 of 2014 concerning Halal Product Guarantee, which states "products that enter, circulate, and trade in Indonesian territory must be certified halal" and this article came into effect on October 17, 2019. However, there are still many MSME (Micro, Small, and Medium Enterprises) who do not have a halal certificate due to cost constraints. etc. The purpose of this study was to evaluate and find answers related to the effect of determining costs and procedures for obtaining a halal certificate on the ease of doing business for businessmen in Makassar City. This research is an empirical research, both quantitative data and qualitative data were analyzed using a qualitative descriptive approach. The results of the study indicate that the determination of costs and procedures for obtaining a halal certificate greatly influences the ease of doing business for businessmen in Makassar City, especially MSME. Of the 60 MSME who have filled out this research questionnaire, 38 MSME (63.3%) admitted that determining the costs and procedures for obtaining a halal certificate was burdensome/complicated for MSME and 22 other MSME (36.7%) claimed to make it easier.